Binge Drinking and Risk Taking Behavior Among Adolescent Females in Israel. Issue 4 (22nd October 2015) - Isralowitz, Richard; Reznik, Alexander
Abstract : Purpose: This prospective study examined binge drinking and alcohol‐related problem behavior among Israeli adolescent females attending public school or a residential facility for substance abuse treatment. Problem: Scant information is known about adolescent females, especially those with high‐risk (e.g., school dropout and immigrant origin) characteristics. Methods: The authors hypothesized that school, residential treatment, and mothers' country of origin status are associated with binge drinking and problem behavior. Findings: Females in residential treatment reported higher levels of binge drinking and problem behavior as expected. However, country of origin was not a significant factor differentiating the female adolescents in school or a residential facility. Logistic regression points to current cigarette smoking, ease of purchasing alcohol, unsupervised night activity, low religiosity, and being physically threatened as predictors of binge drinking and problem behavior. Conclusion: The lack of differences based on country of origin status points to acculturation as a possible reason for the homogeneity. Further research is needed to study the impact of acculturation as well as monitor the alcohol use patterns and problems of adolescents over time and across locations to address prevailing needs.